2001
DOI: 10.1007/bf02258375
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal NOS inhibitor that reduces oxidative DNA lesions and neuronal sensitivity increases the expression of intact c-fos transcripts after brain injury

Abstract: In response to oxidative stress, the ischemic brain induces immediate early genes when its nuclear genes contain gene damage. Antioxidant that reduces gene damage also reduces cell death. To study the mechanism of neuronal sensitivity, we investigated the transcription of the c-fos gene after brain injury of the ischemia-reperfusion type using focal cerebral ischemia-reperfusion in Long-Evans hooded rats. We observed a significant (p < 0.01) increase in c-fos mRNA in the ischemic cortex immediately after brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 48 publications
2
26
0
Order By: Relevance
“…We therefore treated the diabetic rats with 3-BNI (30 mg/ kg), a selective nNOS inhibitor immediately after MCAO and found significant reduction in brain infarction and edema volume. The findings are compatible with previous studies using different nNOS inhibitors against cerebral ischemia under normoglycemic conditions (Cui and Liu, 2001;Ding-Zhou et al, 2003;Lu et al, 2011). Further, 3-BNI caused significant reduction in TUNEL positive cells or DNA fragmentation in ischemic penumbral region thus altogether suggesting its potent neuroprotective potential and thereby the involvement of nNOS/NO in the pathogenesis of diabetic stroke.…”
Section: Parameterssupporting
confidence: 93%
See 2 more Smart Citations
“…We therefore treated the diabetic rats with 3-BNI (30 mg/ kg), a selective nNOS inhibitor immediately after MCAO and found significant reduction in brain infarction and edema volume. The findings are compatible with previous studies using different nNOS inhibitors against cerebral ischemia under normoglycemic conditions (Cui and Liu, 2001;Ding-Zhou et al, 2003;Lu et al, 2011). Further, 3-BNI caused significant reduction in TUNEL positive cells or DNA fragmentation in ischemic penumbral region thus altogether suggesting its potent neuroprotective potential and thereby the involvement of nNOS/NO in the pathogenesis of diabetic stroke.…”
Section: Parameterssupporting
confidence: 93%
“…3-BNI was prepared and sonicated as suspension with ground nut oil at the dose volume of 2 ml/kg. These different doses of 3-BNI were chosen based on literature reports (Cui and Liu, 2001;Gorlach et al, 2000). The neuroprotective potential of 3-BNI was evaluated in randomly grouped diabetic rats post 22 h of reperfusion as described below as compared to vehicle treatment.…”
Section: Drug Preparation and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…c-Fos is an exquisitely sensitive sensor involved in detection of a broad range of modulations of neuronal homeostasis and activity [48, 49, 50, 51]. Notably, a recent study reported that in a mouse model of hypoxia, c-Fos response was exacerbated in the Ngb knockout mouse brain compared to wild-type, suggesting that Ngb deficiency lowers the threshold for hypoxic brain injury [52].…”
Section: Discussionmentioning
confidence: 99%
“…Because c-Fos is a key stress sensor in the nervous system (Cui, Liu, 2001), we asked whether the magnitude of c-Fos induction might inform on differences in oxidative stress levels in the wild type and Ngb-tg brains challenged by acute exposure to combustion smoke. Real-Time qPCR analyses revealed a nearly 300% induction of c-Fos mRNA in the wild type brain, versus only 180% in Ngb-tg at the 1-hour recovery time, and approximately 250%- and 120% at 24-hour recovery post smoke for wild type and Ngb-tg, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%